CIPP Model as a Mathematics Learning Evaluation Model in Elementary School - Laila Qadriah; Muhammad Bagus Adi Wicaksono; Sigit Somadiyono; Hepsi Nindiasari (International Journal of Science and Society, 2022)
The development of learning mathematics can be seen through the implementation of the evaluation. The CIPP evaluation model is one of the models used to evaluate mathematics learning. This research aims to see the results of the evaluation of the mathematics learning process in elementary school X by using the CIPP model. The approach in this research is through a qualitative approach with an evaluative method. The study results found that in terms of context, the quality and suitability of the objectives of learning mathematics were already in a good category. Then the evaluation of the inputs saw how the goals of the mathematics learning program from the scope of students, teachers, materials, and facilities and infrastructure were in very good condition. Furthermore, evaluation in the process that sees how the requirements of the implementation of learning are in a good category. Finally, the product evaluation looks at the student’s learning achievement and the teacher’s learning tools, where this evaluation is also in the very good category.